Marketing analysis of the intelligent urban mobility market - I. Yu. Okolnishnikova; E. V. Krasnov; Yu. G. Kuzmenko (Вестник университета)
The article presents the results of a marketing analysis of the global and Russian markets for intelligent urban mobility, including a set of solutions that improve the quality of citizens’ life – environmentally friendly modes of transport, shared services, on-demand mobility and infrastructure for integrating technologies into the urban environment. The authors propose a characteristic of the smart mobility market, consider the main segments and identify key trends in its development. Special attention is paid to the peculiarities of the transport sharing market development. In a comparative way, the features of consumer preferences, the volume of investments in sharing products and forecasts of market development are analyzed.